2015
DOI: 10.1515/med-2015-0086
|View full text |Cite
|
Sign up to set email alerts
|

Our experience of liver Epithelioid Hemangioendothelioma: from a misdiagnosis to liver transplantation with long term follow-up

Abstract: Malignant Hepatic Epithelioid hemangioendothelioma (HEHE) is an uncommon vascular tumor of intermediate malignant potential. HEHE is a rare tumor and it is difficult to diagnose for surgeons, hepatologists, radiologists and pathologists. So, misdiagnosis with a delay of the treatment is not uncommon.We describe a case of a young woman with a diagnosis of HEHE made 6 years after the first evidence of liver mass with a very long term follow-up after surgical treatment.She had two diagnoses of Hepatocellurar carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…We summarized 14 studies that reported on LT for HEH (Table ) . While there were cases where death occurred shortly after LT due to early recurrence, there were also cases of long‐term survival even if recurrence was observed after LT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We summarized 14 studies that reported on LT for HEH (Table ) . While there were cases where death occurred shortly after LT due to early recurrence, there were also cases of long‐term survival even if recurrence was observed after LT.…”
Section: Discussionmentioning
confidence: 99%
“…We summarized 14 studies that reported on LT for HEH ( Table 2). [8][9][10][11][12][22][23][24][25][26][27][28][29][30] While there were cases where death occurred shortly after LT due to early recurrence, there were also cases of long-term survival even if recurrence was observed after LT. In the cases with long-term survival, the time to recurrence was longer; thus, the tumor's malignant potential may have been lower.…”
Section: Discussionmentioning
confidence: 99%